Peran BPOM dalam Melakukan Pengawasan terhadap Pangan Tanpa Izin Edar - Tresya Tresya (Wajah Hukum, 2018)
Food is a basic need as the right of every human being and as one of the determinants of the quality of human resources. Nutritional imbalances due to unsure food consumption have an impact on public health as consumers. This study aims to find out and analyze the security of the food and the role of the BPOM as a party that assists in monitoring food security. The method used is an approach in this approach method, the author employs an empirical juridical approach, namely research conducted on existing legal facts by conducting research directly into the field to determine the implementation and problems that arise.